The register-functional approach to grammatical complexity theoretical foundation, descriptive research findings, application - Biber, Douglas 1952-; Gray, Bethany ca. 20./21. Jh; Staples, Shelley; Egbert, Jesse 1985- (Routledge, Taylor & Francis Group, 2022)
"This collection brings together the authors' previous research with new work on the Register-Functional (RF) approach to grammatical complexity, offering a unified theoretical account for its further study. The book traces the development of the RF approach from its foundations in two major research strands of linguistics: the study of sociolinguistic variation and the text-linguistic study of register variation. Building on this foundation, the editors demonstrate the RF framework at work across a series of corpus-based research studies focused specifically on grammatical complexity in English. The volume highlights early work exploring patterns of grammatical complexity in present-day spoken and written registers as well as subsequent studies which extend this research to historical patterns of register variation and the application of RF research to the study of writing development for L1 and L2 English university students. Taken together, along with the addition of introductory chapters connecting the different studies, the volume offers readers with a comprehensive resource to better understand the RF approach to grammatical complexity and its implications for future research. The volume will appeal to students and scholars with research interests in either descriptive linguistics or applied linguistics, especially those interested in grammatical complexity and empirical, corpus-based approaches"--
Keywords: Register -- Linguistik; Korpus -- Linguistik; Grammatik; Englisch; Komplexität; Complexity (Linguistics); Register (Linguistics); Corpora (Linguistics); Essays